The relationship of budgetary process in management accounting techniques and job performance / Masnawaty Sangkala and Mansyur Sain - Sangkala, Masnawaty; Sain, Mansyur (2010)
Economic globalization of this magnitude can lead to local adoption of management techniques that have proven useful in other parts of the world. Yet, cultural differences may cause some management accounting techniques that work in one region to be less effective in others, perhaps because of behaviorally related consequences of those techniques. Since culturally different management can react differently to techniques, designers of management control systems may need to consider carefully the issue of potentially "incompatible" techniques, the budgetary process is included in those techniques that are not always compatible with a new environment (Nur Indriantoro, 1993).